a Pengembangan Model Latihan Keterampilan Servis Sila Dalam Permainan Sepak Takraw: Model Latihan Keterampilan Servis Sila Dalam Permainan Sepak Takraw - Sardiman, Sardiman; Kristanti Liloi, Delvi; Kungku, Chiristian (Jurnal Porkes, 2024)
The purpose of this research is to develop a training model for sila service skills. This research is a type of Research and Developmen (R&D) research. The population in this study was 100 people and the sample was a small scale of 15 people and a large scale of 30 people. The instrument used is a value scale questionnaire. The procedure for developing this sila service training model used is the Borg and Gall development which consists of 10 steps. The results that have met the criteria are used, namely: 1) media experts obtained a percentage score of 90.38%, learning experts obtained a percentage score of 90.38%, expert trainers obtained a percentage score of 72.5%, small group students obtained a percentage score of 71.90%, and large group students obtained a percentage score of 78.86%. The results of analyzing student response data after conducting product trials resulted in a percentage score of 78.86% with the criteria used. Which means it is feasible to use in learning or extracurricular activities of sepak takraw games. From the development results it is concluded that the sila service training model can be used and practiced by students.